Exposure to verbal abuse and neglect during childbirth among Jordanian women. (March 2018) - Alzyoud, Fatima; Khoshnood, Kaveh; Alnatour, Ahlam; Oweis, Arwa
Abstract: Women's relationship with health care providers in maternity settings during childbirth has a significant impact on their wellbeing and lives. The current study aims to explore women exposure to neglect and verbal abuse during childbirth Method: a retrospective cross-sectional descriptive design was conducted at four governmental Maternal and Child Health Centers (MCHCs). A final sample of 390 Jordanian women who gave birth within the last 1–3 months was included in the study. Childbirth Verbal Abuse and Neglect Questionnaire (CVANQ) were developed to collect the data. Results: women's age ranged between 18–45 years, and the mean age was 28 year. 32.2% women reported neglect during their last childbirth, 37.7% women reported verbal abuse during last childbirth. Women who reported being neglected also reported being verbally abused. An inverse relationship was found between age and neglect and verbal abuse. Neglect was significantly associated with women's receiving information regarding their rights and responsibilities, being attended by health care providers. Additionally, verbal abuse was significantly associated with being attended by health care provider. Conclusion: child birthing women participated in the current study was exposed to neglect and verbal abuse. This is the first study to report the prevalence of neglect and verbal abuse among child birthing women in Jordan. Research studies is needed to identify the consequences of exposure to neglect and verbal abuse during childbirth on women's psychological, emotional, and physical well being. Training classes and education for health care providers about how to care and communicate with child birthing women. Highlights: High prevalence of women experienced neglect and verbal abuse during childbirth. Women who reported being neglected also reported being verbally abused. An inverse relationship was found between age and neglect and verbal abuse. Verbal abuse was significantly associated with being attended by health provider.